Pengaruh Implementasi Manajemen Sarana dan Prasarana Sekolah dalam Mewujudkan Link and Match dengan Dunia Industri di SMK Pelayaran Muhammadiyah Tuban - Eva Rusmita Anggraeni; Suyanto Suyanto; A. Faizin (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2026)
This research aims to comprehensively analyze and describe the implementation of school facilities and infrastructure management in an effort to realize the "link and match" concept with the shipping industry, specifically at SMK Pelayaran Muhammadiyah Tuban. In the context of vocational education, the alignment between school-based learning facilities and the real-world demands of the workforce is a primary key to producing competent and job-ready graduates. This study employs a qualitative descriptive approach, where data collection techniques were conducted through field observations, in-depth interviews with school stakeholders, and relevant documentation studies. The results indicate that the management of facilities and infrastructure at SMK Pelayaran Muhammadiyah Tuban is implemented systematically through four main stages: (1) requirement planning synchronized with the shipping industry curriculum; (2) procurement of practice facilities based on industry standards and maritime regulations; (3) periodic maintenance and repairs to ensure equipment readiness; and (4) evaluation of facility effectiveness conducted participatively between the school and industry partners. The implementation of the "link and match" strategy is realized through formal cooperation with shipping companies, structured industrial work practices (Prakerin), and the utilization of advanced simulation facilities such as bridge simulators and engine room trainers. Despite facing challenges such as budget constraints and rapid technological updates, this research emphasizes that strategic partnerships and adaptive facility management are crucial for ensuring that maritime education remains relevant to the dynamics of the global labor market.